Speech By Brig. Jen. Dato’ Prof. Dr. Kamarudin Hussin Vice Chancellor of UniMAP during the Academic Talk by Mr. Peter Hoffman. - Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
The Academic Talk by Mr. Peter Hoffmann was held on 23nd September 2011 at Dewan Keikhlasan, Bangunan KWSP, Kangar, Perlis, Malaysia.